Chronic stress predicts post-traumatic stress disorder symptoms via executive function deficits among urban American Indian children. (2nd January 2022) - Kim, Juyoung; Li, Longfeng; Korous, Kevin M.; Valiente, Carlos; Tsethlikai, Monica
Abstract: Little is known about how chronic exposure to stress affects mental health among American Indian (AI) children. The current study aimed to fill this gap by exploring if hair cortisol concentration (HCC), an indicator of chronic stress, predicted post-traumatic stress disorder (PTSD) symptoms through deficits in executive function (EF) skills commonly referred to as inhibitory control, working memory, and cognitive flexibility. A total of 163 urban AI children between 8- and 15-years old participated in the study (92 girls, 56.4%; M age = 11.19, SD  = 1.98). Chronic stress was measured as the concentration of cortisol in children's hair. EF deficits and PTSD symptoms were reported by primary caregivers using the Behavior Rating Inventory of Executive Function and the Trauma Symptom Checklist for Young Children. The results demonstrated that higher HCC was indirectly associated with more PTSD symptoms through deficits in EF skills. Specifically, higher levels of HCC were related to more symptoms of PTSD arousal through impaired working memory, and more symptoms of PTSD avoidance and Intrusion through deficits in cognitive flexibility. The findings suggest interventions that reduce or buffer chronic stress, or that focus on improving EF skills, may promote not only cognitive development but also the mental health of AI children.